Bi-mediated allylation of aldehydes in [bmim][Br]: a mechanistic investigation - Koli, Mrunesh; Chatterjee, Sucheta; Chattopadhyay, Subrata; Goswami, Dibakar (Beilstein Journal of Organic Chemistry, 2018)
The inexpensive room temperature ionic liquid (RTIL), [bmim][Br] has been found to be a superior medium for the Bi-mediated Barbier-type allylation of aldehydes compared to other conventional solvents. It plays the dual role of a solvent and a metal activator enabling higher yields of the products in a shorter reaction time using stoichiometric/near-stoichiometric amounts of reagents. Plausibly, [bmim][Br] activates Bi metal by a charge transfer mechanism. The 1H VT-NMR studies suggested that both the allylating species, allylbismuth dibromide and diallylbismuth bromide, are generated in situ.
Keywords: allylation; bismuth; [bmim][Br]; ionic liquid